European monetary unification and its meaning for the United States - Krause, Lawrence B.; Salant, Walter S. (Washington : Brookings Institution, 1974)
The book is a proceeding on the conference on the implications of European Monetary Integration for the United States, Brookings Institution, 1972 and European monetary unification and its meaning for the United States held in Washington, Brookings Institution in1974.
Includes bibliographical references.
usc 19/10/18
Loans
Keywords: Monetary policy; Foreign exchange; Monetary unions; Europe--European Economic Community countries